(untitled) (Global Journal of Science Frontier Research, 2018)
In these decades, digital communication and data which is collected in social media have been increased rapidly. Social network and social media have been presented the more updating compared to traditional media. Many approaches to analyze data in social media have been proposed. In this regards, data and information from social media should be provided as posts, comments in the text format. Using data and information from social media have some dissatisfaction including fake news, disinformation, comments lack of humanity, contrary to social standards. In this paper, we proposed a method to analyze text’s content in social media. Besides, we proposed a system to collect and analyze text’s content data in social media. In additional, we provide a model to orient social media and social network management.